Estimating Policy-Corrected Long-Term and Short-Term Tax Elasticities for the United States, Germany, and the United Kingdom - Bernd Hayo; Sascha Mierzwa; Umut Unal (Philipps-University Marburg, School of Business and Economics, 2021)
We estimate the elasticities of the most important tax categories using a new quarterly database of discretionary tax measures for the United States, Germany, and the United Kingdom over the period 1980Q1 to 2018Q2. Employing Romer and Romer's (2009) narrative approach, we construct a policy-neutral dataset based on revenue figures from governmental records. Using this quantitative information, we are able to subtract policy-induced changes, which are typically not considered in the extant literature. Furthermore, we estimate state-dependent elasticities. Our conclusions are as follows. (i) In Germany and the UK, long-term tax-to-base elasticities are generally higher than short-term elasticities, whereas results for the US are mixed. (ii) Short-term base-to-output elasticities tend to be smaller than unity, whereas long-term elasticities are close to unity. (iii) German and UK tax-to-output elasticities in the short term are lower than long-term elasticities, with mixed results for the US. (iv) For tax-to-base elasticities, we find business cycle asymmetries across countries but not within countries. (v) For base-to-output elasticities, our results suggest few asymmetries across countries and more asymmetries across tax types. (vi) Typically, the above conclusions do not hold for corporate income tax.
Keywords: E62; H20; H30; E32; 330; Tax revenue; tax base; tax elasticity; business cycle; Germany; United Kingdom; United States